Coaching for emotional intelligence : the secret to developing the star potential in your employees - Wall, Bob (Bob Lee) (Amacom, 2007)
Coaching too often focuses entirely on job performance. While important, performance coaching does not do very much to develop exceptional talent or nurture overall growth. This book gives managers the tools to help employees make the leap from solid performer to superstar. It demonstrates how managers can leverage and develop such factors as personality traits, communication styles, and personal behaviors. It gives a clear, accessible, and practical approach to an often elusive subject.